Dr. Franc Pediček - naš učitelj - Krevsel, Viktor (Šport (Ljubljana), 2013)
The history of the Faculty of Sport in Ljubljana has some shiny and also grey spots in the period of its establishment. One of such grey spots is the period when Prof. Franc Pediček worked as a professor of psychology and pedagogy and was actively engaged at the then Institute of Physical Education (ITV). In 1955 I enrolled at the then Institute. When students enrolled, they were promised that during their schooling the Institute would be transformed into a higher education institution. The index of the Institute for Physical Education proves that Prof. Pediček delivered two lectures of psychology per week in the first semester and another two lessons of pedagogy in the second semester.
Keywords: Fakulteta za šport; pedagogi; pedagogika; pedagogy; Pediček, Franc, 1922-2008; sport; šport; športna vzgoja; telesna kultura; telesna vzgoja